Assessing the feasibility of replacing a specific diesel truck with a Battery Electric Vehicle using the Operating Cycle format - Emvin, Carl (My University, 2023)
While facing continuously stricter legislation due to the threat of global warming, vehicle manufacturers strive to find alternative means of transportation such as the Battery Electric Vehicle (BEV). While doing so, uncertainties regarding performance are halting the shift to more sustainable alternatives. This thesis will therefore build a framework for retailers to predict and estimate to which degree a BEV can replace a fossil-driven vehicle in specific missions. The framework will try to describe the details of transport missions while remaining relatively computationally light. This framework developed within the COVER project is called Operating Cycle (OC). It is a description of a road transport mission with an adequate level of detail that captures the physical and practical phenomenon of a transport mission. It can be divided into two sub-descriptions, the deterministic Operating Cycle (dOC) and stochastic Operating Cycle (sOC), which are the representations adopted in this thesis. Using vehicle log data from a specific Internal Combustion Engine Vehicle (ICEV), the OC format is extended to include models for Payload, Mission stop and EV-Recharging. Using the models of the OC format, a feasibility analysis of replacing a specific vehicle with a BEV is conducted. The resulting analysis shows that the current BEV fleet is not able to complete all the missions that the ICEV completed without alteration of specific transport missions.
Keywords: Operating Cycle; Stochastic modelling; Transport mission; Battery Electric Vehicle; Depth of Discharge; State of Charge; deterministic Operating Cycle